Analisis Kelebihan dan Kekurangan dalam Teknik Animasi Comic Book Look pada Animasi “Arcane” - Indra Febrianto Nugroho (Jurnal Ilmiah Wahana Pendidikan, 2023)
3D animation is currently on the rise in modern cinema circles lately. Coupled with online streaming platforms, access to watching movies from home is even easier. One of the well-known 3-D animations and won the best animation award in 2022 is the animated series "Arcane" which airs on the online streaming platform Netflix. Animated film "Arcane" uses an animation technique called Comic Book Look, where this technique makes 3D animation look like 2D animation. This analysis aims to further examine the Comic Book Look technique that is currently popularly used in the world of 3D animation lately such as "Into the spider verse", "Arcane" and "Puss in Boot: The Last Wish", as well as find out more about the advantages, disadvantages and solutions to the problems found in the animation technique.